Parametric investigation on the performance of a direct evaporation cooling battery thermal management system. (15th June 2022) - Wang, Zhengkun; Wang, Yanan; Xie, Zongfa; Li, Hua; Peng, Weili
Highlights: A battery model considering the current density distribution is employed. Direct cooling can significantly reduce the MAT on the cell. Increasing flow velocity, thermal conductivity and latent heat can reduce the MAT. Decreasing initial temperature and saturation temperature can reduce the MAT. Abstract: Lithium-ion batteries will produce a lot of heat during charging and discharging. If the heat cannot be exported in time, it will significantly increase the temperature and temperature difference in the battery system, which can seriously affect the capacities, lives and safety of the batteries. Direct evaporation cooling is a new and efficient battery thermal management method. It is necessary to comprehensively understand the effects of its design and operation parameters on the performance of the battery thermal management system. In this paper, a direct evaporation cooling battery thermal management system was designed with the refrigerant of R134a. The electric-thermal coupled model of the lithium-ion battery was used, which considered the current density distribution in the battery. The performance of the battery thermal management system was obtained by numerical simulation based on the transient VOF method. It was found that compared to air natural convection cooling and liquid cooling, direct evaporation cooling could significantly reduce the maximum temperature on the cell under the 3 C discharging condition. The effects of the initial temperature, flow velocity, saturation temperature, thermal conductivity, and latent heat of the refrigerant on the performance of the battery thermal management system were further investigated. It could provide theoretical references and technical means for the design and analysis of the direct evaporation cooling battery thermal management system in the future.